Laboratory Tests Used in the Diagnosis of Immune Thrombocytopenia and General Treatment Approaches - Ozcelik, Fatih; Keskin, Umran; Kılıçaslan, Emrah; Kale, Ebru (Journal of Hematology and Oncology Research, 2020)
Immune thrombocytopenia currently called under its’ new name, immune thrombocytopenic purpura (ITP) is a disease characterized by thrombocytopenia, in which the body attacks its own platelets due to the disorders in immune system. The pathophysiology of this disease includes increased platelet destruction and most megakaryocyte production in bone marrow. The most common clinical manifestation of ITP is mild or severe progressive bleeding that could result in death. ITP is generally named as primary or secondary ITP according to thrombocytopenia severity, disease duration, bleeding status and secondary occurrence of the disease. Currently for diagnosis, despite the blood count, antiglobulin test and laboratory tests that can detect platelet-bound antibodies, they are not enough for definitive diagnosis. Like the difficulty in diagnosis, ITP treatment is quite complicated which varies depending on age, characteristics and risk of the patient. It is classified as first, second and third-line treatment options. Also, depending on the condition of patients, combined treatment might be an option which increases the complexity of the treatment. Unfortunately, discussions related to different clinical applications in diagnosis and treatments continue recently. For this reason, we considered that preparation of a review containing recent updates in diagnostic approaches and treatment options in ITP will be remarkable and beneficial for physicians interested in this subject.
Keywords: Immune thrombocytopenia; Coombs Test; Thrombopoietin Receptor Agonists; Intravenous Immunoglobulin; Rituximab